1991
DOI: 10.1016/0002-9343(91)90451-3
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose octasulfate stimulates gastric somatostatin release

Abstract: To explore the mechanisms of the effects of sucralfate on the stomach, we investigated the action of sucrose octasulfate (SOS), a constituent of sucralfate, on the function of canine gastric parietal cells and somatostatin cells and in the isolated perfused intact rat stomach. Somatostatin cells from the canine gastric fundus were isolated by EDTA-collagenase dispersion and counterflow elutriation, and somatostatin-like immunoreactivity (SLI) release in response to SOS was measured by radioimmunoassay. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…There is also some evidence that endogenous sulphydryl groups within the gastric mucosa may contribute to the protective action of sucralfate on the vascular network (16). Lucey et al (8) have shown that sucrose octasulphate releases somatostatin from gastric D cells (8). The significance of this finding remains uncertain but may be important in modulating both parietal cell activity and gastric mucosal blood flow.…”
Section: Sucralfate and The Mucosal Defense Mechanismsmentioning
confidence: 96%
“…There is also some evidence that endogenous sulphydryl groups within the gastric mucosa may contribute to the protective action of sucralfate on the vascular network (16). Lucey et al (8) have shown that sucrose octasulphate releases somatostatin from gastric D cells (8). The significance of this finding remains uncertain but may be important in modulating both parietal cell activity and gastric mucosal blood flow.…”
Section: Sucralfate and The Mucosal Defense Mechanismsmentioning
confidence: 96%
“…Eine positive Wirkung von Sucrose Octasulfat auf die Wundheilung wurde erstmalig in vitro an humanen Ösophagusepithelzellen und isolierten Rattenmägen in den 1990er-Jahren nachgewiesen [7,8]. Darauf folgende Versuche beispielsweise am Kaninchen-Augenmodell bestätigten die positiven Ergebnisse [9].…”
Section: Sucrose Octasulfatunclassified